2006
DOI: 10.1182/blood-2006-02-001578
|View full text |Cite
|
Sign up to set email alerts
|

Noninfectious papilloma virus–like particles inhibit HIV-1 replication: implications for immune control of HIV-1 infection by IL-27

Abstract: Human papilloma virus (HPV)- IntroductionIt has been demonstrated that both innate and adaptive immune response regulate HIV-1 replication, 1-10 and certain cell types secrete soluble HIV-1-suppressing proteins in response to various stimuli. [11][12][13][14][15] For example, secretion of anti-HIV ␤-chemokines and CD8 antiviral factor (CAF) from human T-lymphotropic virus (HTLV)-type 1 and herpes virus saimiri-infected cell line have been described. [11][12][13][14][15] Although a combination of antibodies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(128 citation statements)
references
References 65 publications
5
123
0
Order By: Relevance
“…2), an increased serum level of IL-32 might result in the acceleration of HIV-1 replication or spread in vivo. Recently, IL-27 has been shown to inhibit HIV-1 replication in macrophages (38,39). Interestingly, we found that M-CSF also significantly reduced the anti-HIV-1 activity of IL-27 (data not shown).…”
Section: Discussionmentioning
confidence: 61%
“…2), an increased serum level of IL-32 might result in the acceleration of HIV-1 replication or spread in vivo. Recently, IL-27 has been shown to inhibit HIV-1 replication in macrophages (38,39). Interestingly, we found that M-CSF also significantly reduced the anti-HIV-1 activity of IL-27 (data not shown).…”
Section: Discussionmentioning
confidence: 61%
“…Treatment of monocytes and T cells with IL‐27 induces BST‐2 in an IFN signaling‐independent manner 154. IL‐27 is a cytokine produced by myeloid cells 155 and functions to inhibit HIV‐1 replication in various cell types 156, 157, 158. Whether BST‐2 is one of the effectors of anti‐HIV‐1 activity of IL‐27 is yet to be determined.…”
Section: Bst‐2 Regulationmentioning
confidence: 99%
“…Rabbit polyclonal antibody to APOBEC3G and mouse monoclonal antibody to HIV-1 Vif were obtained from Abcam (Cambridge, MA). Peripheral blood mononuclear cells (PBMCs) were isolated from healthy donors by Ficoll-Hypaque centrifugation, as previously described (11). CD4 ϩ T cells were purified from PBMCs using CD4 microimmunomagnetic beads (Miltenyi Biotec, Auburn, CA) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…These include HLA-type (1)(2)(3)(4), HIV co-receptor expression (5), the cytidine deaminase APOBEC3G (6,7), tetherin (BST-2) (8), SAMHD1 (9,10), and an array of cytokines. Some cytokines such as type 1 and type 3 interferons, chemokines (e.g., stromal cell-derived factor 1, macrophage inflammatory factor 1a, RANTES (regulated on activation normal T cell expressed and secreted), and IL-27) inhibit HIV replication (11)(12)(13), whereas some enhance replication (IL-6 (14), tumor necrosis factor-␣ (15), IL-12 (16), and colony-stimulating factors (17,18)), and some are capable of either inhibiting or enhancing replication depending upon the culture system and conditions. In this regard, IL-2 has been shown to be capable of suppressing HIV-1 replication through the enhancement of CD8ϩ T cell function and enhancing HIV-1 replication in primary cultures of CD4ϩ T cells (19 -21).…”
Section: Il-2 Has Been Used In Culture Of Primary T Cells To Maintainmentioning
confidence: 99%